On-ice physical demands of world-class women`s ice hockey: From training to competition - Douglas, A.; Rotondi, M. A.; Baker, J.; Jamnik, V. K.; Macpherson, A. K. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To compare on-ice external and internal training loads in world-class women's ice hockey during training and competition. Methods: On-ice training loads were collected during 1 season from 25 world-class ice hockey players via wearable technology. A total of 105 on-ice sessions were recorded, which consisted of 61 training sessions and 44 matches. Paired and unpaired t tests compared training and competition data between and across playing positions. Results: For training data, there was a difference between positions for PlayerLoad (P < .001, effect size [ES] = 0.32), PlayerLoad·minute-1 (P < .001, ES = 0.55), explosive efforts (P < .001, ES = 0.63), and training impulse (P < .001, ES = 0.48). For the competition data, there were also differences between positions for PlayerLoad (P < .001, ES = 0.26), PlayerLoad·minute-1 (P < .001, ES = 0.38), explosive efforts (P < .001, ES = 0.64), and training impulse (P < .001, ES = 1.47). Similar results were found when positions were viewed independently; competition had greater load and intensity across both positions for PlayerLoad, training impulse, and explosive efforts (P < .001, ES = 1.59-2.98) and with PlayerLoad·minute-1 (P = .016, ES = 0.25) for the defense. Conclusions: There are clear differences in the volume and intensity of external and internal workloads between training and competition sessions. These differences were also evident when comparing the playing positions, with defense having lower outputs than forwards. These initial results can be used to design position-specific drills that replicate match demands for ice hockey athletes.